Surface cationic functionalized nano-hydroxyapatite – Preparation, characterization, effect of coverage on properties and related applications. (5th June 2020) - Timpu, Daniel; Sacarescu, Liviu; Vasiliu, Tudor; Dinu, Maria Valentina; David, Geta
Graphical abstract: Highlights: Functionalized nHAp was obtained using arginine or polyethylenimine. Resulted nanoparticles were comparatively characterized relative to used modifiers. Linear polyethylenimine coated hydroxyapatite had the best DNA binding ability. Use of LPEI functionalized nHAp in biocomposites recipe had a strengthening effect. The 3D constructs demonstrated rapid self–recovery and fatigue resistant behavior. Abstract: Functionalized nano-hydroxyapatite (nHAp) was obtained by wet chemical technique, using arginine (Arg) or polyethylenimine (branched-bPEI, or linear-LPEI) as cationic modifiers and dispersing agents. TEM, FT-IR, SEM, DLS and WAXD characterization results showed that the prepared nanoparticles possessed needle- or plate-like morphologies and Arg and PEI were successfully grafted onto nHAp. LPEI functionalized nHAp exhibited a good similitude with biological apatite and the best DNA binding ability. In addition, the incorporation of nHAp/LPEI nanoparticles within collagen/dimethylsilanediol hyaluronate-based porous matrices pointed out a significant improvement of the compressive modulus of biocomposites: up to a six-fold increase, compared with the polymer matrix without fillers. Moreover, the composite sponges revealed high toughness during five consecutive compression tests without any permanent deformation and cracks. Therefore, nHAp/LPEI nanoparticles could be considered promising materials for biomedical applications, like gene carrier or reinforcement filler with strong interfacial adhesion in biocomposites for bone engineering.